Effect of PGPR, Phosphate sources and vermicompost on growth and nutrients uptake by lettuce in a calcareous soil. (2nd January 2018) - Khosravi, Anahita; Zarei, Mehdi; Ronaghi, Abdolmajid
ABSTRACT: In order to study the effect of plant growth promoting rhizobacteria (PGPR), vermicompost and phosphate sources on the growth and nutrients uptake by lettuce, a greenhouse experiments was conducted. Treatments consisted of PGPR ( Pseudomonas fluorescens ) (with and without inoculation), vermicompost (0 and 1% w/w) and phosphate sources (control, rock phosphate (RP), tricalcium phosphate and triple super phosphate (TSP) at 25 mg P kg −1 level). Biological fertilizers, RP and TSP significantly increased shoot dry matter (SDM) and some measured nutrients uptake. Co-application of PGPR and RP, in non-vermicompost treatments significantly increased SDM, shoot nitrogen, phosphorus (P), potassium, zinc and manganese uptake rates. Shoot P uptake had no significant difference between TSP and RP treatments. Co-application of PGPR, vermicompost and TSP significantly decreased SDM, which may be due to the P toxic levels in the plant aerial parts and/or the inhibition of the bacterial activities in the rhizosphere soil.